Sebuah Laporan Kasus Manajemen Anestesi pada Lansia dengan Peritonitis Sekunder: Sebuah Laporan Kasus - Saputra, Baridi Adlan; M. Hidayatullah Saputra Amsia; Luthfi, Ahmad Angga (Medula, 2024)
Thyroid carcinoma is the most common malignancy of the endocrine system and ranks 9th out of the 10 most common cancers in Indonesia. Thyroid carcinoma can lead to possible difficulties in airway management and intubation as well as the possibility of thyroid storm although this is rare. Anesthesiologists should pay special attention to the preoperative, perioperative and postoperative measures of patients with thyroid carcinoma because primary tumors or metastases in the head neck, lung or mediastinum region can cause airway obstruction at the level of the larynx, trachea or bronchi. The American Society of Anesthesiologists (ASA) and the Difficult Airway Society (DAS) have created difficult airway and difficult intubation management algorithms to facilitate anesthesiologists in dealing with these conditions. This case report discusses a 55 year old male patient with right thyroid carcinoma who underwent radical neck dissection surgery using a long laryngoscope blade number 4. The patient was successfully intubated and underwent surgery with normal hemodynamic monitoring. The importance of good and correct preoperative, intraoperative and postoperative management, especially with regard to airway management, will make the operation run smoothly and safely and reduce morbidity and mortality in patients.